2011
DOI: 10.3892/mmr.2011.546
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOE polymorphisms and insulin resistance with TCM syndromes in type 2 diabetes patients with macroangiopathy

Abstract: Abstract.To investigate the association between apolipoprotein E (APOE) polymorphisms and insulin resistance and Traditional Chinese Medicine (TCM) syndromes in type 2 diabetes mellitus (T2DM) with macroangiopathy, 60 patients with T2DM macroangiopathy were enrolled and divided into three groups: dryness-heat due to deficiency of yin, Qi-Yin deficiency, and Yin-Yang deficiency, according to the TCM syndromes, with a control group of 20 healthy individuals. APOE genotype analysis was performed with polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…The observations include: the linkage between sex hormones and Shen deficiency syndrome was identified in chronic nephritis (Zhang et al, 1990); between C-reactive protein and Han/Re (cold/hot) syndrome in rheumatoid arthritis (RA) (Zhao et al, 2006); between Qi-Yin deficiency syndrome in type 2 diabetes mellitus patients (Xie et al, 2011); between carotid intima-media thickness (IMT), triglyceride (TG) and blood rheology with certain TCM syndrome (Lei et al, 2009); between blood stasis syndrome score with 24-h urine protein ration, cholesterol, estimation of glomerular filtration rate (eGFR) in the primary glomerular diseases ; between the bone mineral density and Shen deficiency syndrome in chronic obstructive pulmonary disease (COPD) ; between serum level of eosinophil cationic protein in asthmatic patients and the development of "heat" syndrome manifestations (Hsu et al, 2003); between the decrease in skin electrical conductance and the severity of Qi deficiency syndrome (Yu et al, 1998). More studies are in progress to explore the correlations between TCM syndrome and the biological indexes.…”
Section: Syndrome Differentiation and Modern Research In Tcm Diagnosismentioning
confidence: 97%
“…The observations include: the linkage between sex hormones and Shen deficiency syndrome was identified in chronic nephritis (Zhang et al, 1990); between C-reactive protein and Han/Re (cold/hot) syndrome in rheumatoid arthritis (RA) (Zhao et al, 2006); between Qi-Yin deficiency syndrome in type 2 diabetes mellitus patients (Xie et al, 2011); between carotid intima-media thickness (IMT), triglyceride (TG) and blood rheology with certain TCM syndrome (Lei et al, 2009); between blood stasis syndrome score with 24-h urine protein ration, cholesterol, estimation of glomerular filtration rate (eGFR) in the primary glomerular diseases ; between the bone mineral density and Shen deficiency syndrome in chronic obstructive pulmonary disease (COPD) ; between serum level of eosinophil cationic protein in asthmatic patients and the development of "heat" syndrome manifestations (Hsu et al, 2003); between the decrease in skin electrical conductance and the severity of Qi deficiency syndrome (Yu et al, 1998). More studies are in progress to explore the correlations between TCM syndrome and the biological indexes.…”
Section: Syndrome Differentiation and Modern Research In Tcm Diagnosismentioning
confidence: 97%
“…For example, previous genomics studies have found the relationships between interleukin-10 genotype and deficiency ZHENG in hepatitis B cirrhosis [29, 30] and between apolipoprotein polymorphisms and ZHENGs in type 2 diabetes mellitus [55]. Using transcriptomics, Ma et al [22] have indicated that interleukin-8 might be related to the pathobiology of blood stasis ZHENG in cornary heart, and Chen et al [64] have concluded that inflammatory-gene expression (ALOX5AP, S100A8 and S100A12) might be related to Cold ZHENG in hemodialysis.…”
Section: A Literature Analysis For the Clinical Tcm Zheng Differenmentioning
confidence: 99%
“…In hyperlipidemia, it was found that polymorphism of ApoE gene is related in a certain degree to liver-kidney Yin deficiency ZHENG, spleen-kidney Yang deficiency ZHENG, Qi-stagnation-caused blood-stasis ZHENG, and so forth [50]. In diabetes mellitus, ApoE gene polymorphism was also explored, and it has proved that the Qi-Yin deficiency ZHENG in type 2 diabetes mellitus patients with macroangiopathy is associated with the ApoE E4 and E3 genotypes [55]. …”
Section: Applications Of Omics Technologies On Clinical Research Omentioning
confidence: 99%
“…Actually, researchers and scientists of TCM have done some work with a lot of beneficial methods, such as physiology and biochemistry [7], molecular biology [8], and tongue image digitization [9, 10], to classify ZHENGs and evaluate the treatment based on ZHENG classification. Though the researches are beneficial, they are far from satisfactory.…”
Section: Introductionmentioning
confidence: 99%